Transgenerational effects of plant biotic interactions - Puy Gutiérrez, Javier (Jihočeská univerzita, 2020)
This thesis focuses on the transgenerational effects triggered by plant biotic interactions and explores their relevance on ecological and evolutionary processes. The following sections document novel results that show their important consequences on different aspects. Primarily, we established the necessary methodology to be able to explore these questions and to disentangle the mechanisms originating the transgenerational plasticity by validating a demethylation method. Then, we checked whether the biotic interactions alter the phenotype via within-generation and transgenerational plasticity, examining the magnitude and direction of the response on each specific "response traits". Lastly, the potential role of transgenerational plasticity for adaptation, species coexistence, creating biodiversity and population and ecosystem functioning is tested.
Transgenerational effects of plant biotic interactions
Keywords: adaptation; arbuscular mycorrhizal fungi; biotic interactions; biodiversity; coexistence; DNA methylation; drought stress; functional traits; heritable epigenetic plasticity; intraspecific phenotypic variation; parental effects; plant competition; symbiosis; transgenerational effects; Adaptation; Arbuscular mycorrhizas; Biotic interactions; Biodiversity; Coexistence; DNA methylation; Drought stress; Ecosystem functioning; Functional traits; Heritable epigenetic plasticity; Intraspecific phenotypic variation; Parental effects; Plant competition; Plasticity; Stress memory; Transgenerational effects